2015
DOI: 10.1089/gtmb.2015.0077
|View full text |Cite
|
Sign up to set email alerts
|

Association ofACEandMDR1Gene Polymorphisms with Steroid Resistance in Children with Idiopathic Nephrotic Syndrome

Abstract: Screening these polymorphisms will pave the way to better understand the molecular mechanisms of the disease, which may be useful in developing targeted therapies for INS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…[1417,3135] All of the participants in these studies were children consisting of 928 patients with INS and 879 healthy controls; moreover, steroid resistance data were available for 724 patients comprising 488 patients with SS and 236 patients with SR, which were compared. The subjects in 4 studies were Asian [16,17,34,35] and those from the other 5 were Caucasian. [14,15,3133] Seven studies reported genotype frequencies between patients with INS and healthy controls, [1416,31,32,34,35] and 7 studies showed the genotype data of SS and SR groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[1417,3135] All of the participants in these studies were children consisting of 928 patients with INS and 879 healthy controls; moreover, steroid resistance data were available for 724 patients comprising 488 patients with SS and 236 patients with SR, which were compared. The subjects in 4 studies were Asian [16,17,34,35] and those from the other 5 were Caucasian. [14,15,3133] Seven studies reported genotype frequencies between patients with INS and healthy controls, [1416,31,32,34,35] and 7 studies showed the genotype data of SS and SR groups.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects in 4 studies were Asian [16,17,34,35] and those from the other 5 were Caucasian. [14,15,3133] Seven studies reported genotype frequencies between patients with INS and healthy controls, [1416,31,32,34,35] and 7 studies showed the genotype data of SS and SR groups. [1417,32,33,35] Haplotype frequencies of both case and control cohorts were described in part in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genotype frequencies were found to be in Hardy‐Weinberg equilibrium ( χ 2 = 0.330). The allele and genotype frequencies of the study population were compared with that of the healthy population and were found to be similar ( P > 0.05; Table ).…”
Section: Resultsmentioning
confidence: 98%